STRATEGI DINAS PARIWISATA DALAM MENGEMBANGKAN PARIWISATA BERDASARKAN PERATURAN DAERAH KABUPATEN SAMBAS NOMOR 5 TAHUN 2016 TENTANG RENCANA INDUK PARIWISATA (STUDI DI DANAU SEBEDANG) - Lara Kusuma Harni; Zainal Amaluddin; Sri Sudono Saliro (CV. ADIBA AISHA AMIRA, 2025)
Tourism development strategies, particularly around Lake Sebedang. Sambas Regency certainly boasts numerous tourist attractions, but Lake Sebedang is unique in its natural beauty. Therefore, the Sambas Regency government, through the Department of Tourism, Youth, and Sports (Disparpora), is striving to maximize Lake Sebedang's potential, as evidenced by the 500 visitors per month. The research questions are: What is the tourism development strategy for the Lake Sebedang Master Plan, as outlined in Regional Regulation Number 5 of 2016 concerning the Tourism Master Plan, in the Lake Sebedang area? What are the supporting and inhibiting factors of the Tourism Department in Lake Sebedang?. The research approach used by the researcher is qualitative. The purpose of this qualitative research is to generate descriptive data in the form of written or spoken words from observable individuals. This research is field research, which involves collecting data and information directly in the field (the research area). Based on the research results, it was found that: The tourism development strategy, in accordance with Regional Regulation Number 05 of 2016 concerning the Master Plan for the Lake Sebedang area, involves collaboration between the Lake Sebedang tourism management and the Tourism Office, conducting promotions to increase Lake Sebedang's awareness, and maintaining existing facilities at Lake Sebedang in accordance with Regional Regulation Number 05 of 2016 concerning the Master Plan. Supporting and inhibiting factors for the tourism office at Lake Sebedang include government attention, specifically from the Tourism Office. This attention is expressed in the form of assistance and guidance to Lake Sebedang managers. Inhibiting factors include a lack of social media promotion of the attractiveness of Lake Sebedang and the lack of facilities and infrastructure.